2021
DOI: 10.3390/agriculture11070642
|View full text |Cite
|
Sign up to set email alerts
|

Would Kazakh Citizens Support a Milk Co-Operative System?

Abstract: We estimate the monetary value of a policy aimed at increasing rural co-operative production in Kazakhstan to increase milk production. We analyse the drivers associated with public support for such policy using the contingent valuation method. The role of individuals’ psychological aspects, based on the reasoned action approach, along with individuals’ views on the country’s past regime (i.e., to the former Soviet Union), their awareness about the governmental policy, their sociodemographic characteristics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
1
3
1
Order By: Relevance
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
“…However, for the high-cost IICS, farmers' endowment plays an important role. The above conclusions are different from previous studies, which showed that higher endowment usually leads to higher adoption intention [11,17]. For example, the study of Jayne [52], which focused on Africa, found that the adoption level of high-income farmers is high.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Another study estimates the monetary value of a policy aimed at increasing rural cooperative production in Kazakhstan in order to increase milk production [9]. It analyzes the factors associated with public support for such a policy.…”
mentioning
confidence: 99%